2010
DOI: 10.1097/iae.0b013e3181d2f11d
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Ranibizumab Treatment of Macular Choroidal Neovascularization Secondary to Angioid Streaks

Abstract: Intravitreal ranibizumab is highly effective in improving or stabilizing vision and lesion morphology in patients with macular choroidal neovascularization secondary to angioid streaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 37 publications
2
27
1
Order By: Relevance
“…Similar results after a longer follow-up were reported by Martinez-Serrano et al [45] in 14 eyes. In contrast, our data disagree with the data obtained by Sawa et al [31] , Finger et al [34] , El Matri et al [35] , Mimoun et al [24] , Ladas et al [37] , and Shah et al [40] , who demonstrated a trend for improvement or stability of functional and anatomical outcomes in their case series. In the study by Ladas et al [37] , eyes were treated according to a treatand-extend protocol, showing beneficial results with a mean of 7.1 injections over a 16-month period.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Similar results after a longer follow-up were reported by Martinez-Serrano et al [45] in 14 eyes. In contrast, our data disagree with the data obtained by Sawa et al [31] , Finger et al [34] , El Matri et al [35] , Mimoun et al [24] , Ladas et al [37] , and Shah et al [40] , who demonstrated a trend for improvement or stability of functional and anatomical outcomes in their case series. In the study by Ladas et al [37] , eyes were treated according to a treatand-extend protocol, showing beneficial results with a mean of 7.1 injections over a 16-month period.…”
Section: Discussioncontrasting
confidence: 56%
“…Our data showed a lower number of injections. This could be explained by the PRN regimen used in our case series compared with the different retreatment protocol used by Ladas et al [37] . We think that a treat-and-extend protocol may allow better visual and anatomical results, but it imposes a higher burden of intravitreal treatments on patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26][27] Previous studies have demonstrated that ranibizumab has a prolonged effect in either stabilising or improving vision in CNV secondary to AS. 13 19 Vadalà et al 20 reported a series of nine patients who received 0.3 mg ranibizumab injections with a mean follow-up of 14 months. Mean visual acuity increased significantly with eight (88.9%) of the nine patients demonstrating an improvement or stabilisation in vision.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these studies are limited to single case reports, small numbers of patients or have limited/short follow-up. [16][17][18][19][20][21][22] We report a retrospective case series that assesses the medium to long-term efficacy and safety of intravitreal ranibizumab in patients with CNV secondary to AS.…”
Section: Introductionmentioning
confidence: 99%